2020
DOI: 10.1007/s00394-020-02333-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a split portion of flaxseed on 24-h blood glucose response

Abstract: Purpose Flaxseed can be effective at lowering and stabilising blood glucose responses. The aim of this study was to determine whether flaxseed could lower blood glucose response more effectively when consumed as a single portion of 30 g, or a split portion consumed three times per day (10 g flaxseed per portion). Methods The study was a randomised, repeated measures, cross-over design. Fifteen healthy participants consumed either (1) three flaxseed muffins containing a total of 30 g of flaxseed once in the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Diets containing relatively high levels of plant‐derived foods that providing essential protein, lipids, carbohydrates, vitamins and minerals, as well as fibers and other phytonutrients, have been linked to lower risks of various chronic diseases (Carraro et al., 2012; Edel et al., 2015). Indeed, studies suggest that flaxseed consumption can lower the risk of cardiovascular diseases, diabetes, cancer, inflammation, kidney diseases, gastrointestinal disorders, and maintain brain health (Almehmadi et al., 2021; Karantonis et al., 2022; Parikh et al., 2018, 2019; Seedy et al., 2021; Thumann et al., 2019). These health benefits have partly been attributed to the fact that flaxseed is a good source of essential omega‐3 fatty acid, but also high quality of protein, soluble dietary fibers, lignans and multiple phytochemicals, which could exert anti‐inflammatory, antioxidant, antihypertensive, glucose absorption control, immune suppression/enhancement, and so forth (Kaneda et al., 2016; Marambe et al., 2008; Mosavat et al., 2018; Rabetafika et al., 2011; Rodriguez et al., 2013; Silva & Alcorn, 2019; Tang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Diets containing relatively high levels of plant‐derived foods that providing essential protein, lipids, carbohydrates, vitamins and minerals, as well as fibers and other phytonutrients, have been linked to lower risks of various chronic diseases (Carraro et al., 2012; Edel et al., 2015). Indeed, studies suggest that flaxseed consumption can lower the risk of cardiovascular diseases, diabetes, cancer, inflammation, kidney diseases, gastrointestinal disorders, and maintain brain health (Almehmadi et al., 2021; Karantonis et al., 2022; Parikh et al., 2018, 2019; Seedy et al., 2021; Thumann et al., 2019). These health benefits have partly been attributed to the fact that flaxseed is a good source of essential omega‐3 fatty acid, but also high quality of protein, soluble dietary fibers, lignans and multiple phytochemicals, which could exert anti‐inflammatory, antioxidant, antihypertensive, glucose absorption control, immune suppression/enhancement, and so forth (Kaneda et al., 2016; Marambe et al., 2008; Mosavat et al., 2018; Rabetafika et al., 2011; Rodriguez et al., 2013; Silva & Alcorn, 2019; Tang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that flaxseed muffins given thrice a day were more effective than control muffins at reducing and sustaining blood glucose levels over 24 hours. It was observed that Flaxseeds should be consumed in small amounts throughout the day, not all at once [32].…”
Section: Paper-based Informationmentioning
confidence: 99%
“…Even with CGM, the basal glucose levels were generally estimated from few, closely spaced glucose readings gathered under controlled conditions, after an overnight fast; the considered data was for example reduced to one glucose reading ( 13 ), or to the average value estimated from all readings over 30 min ( 14 ), or over 60 min prior to nutritional interventions ( 10 ). In another study where no overnight fast was required ( 15 ), the single glucose reading gathered at 6 am was considered as estimate for basal glucose. In most of these studies ( 10 , 13 , 15 ), basal glucose was estimated for each test day, while in one of these studies ( 14 ), the estimate from the first day was considered for the analysis of all following days.…”
Section: Introductionmentioning
confidence: 99%
“…In another study where no overnight fast was required ( 15 ), the single glucose reading gathered at 6 am was considered as estimate for basal glucose. In most of these studies ( 10 , 13 , 15 ), basal glucose was estimated for each test day, while in one of these studies ( 14 ), the estimate from the first day was considered for the analysis of all following days. These methods, besides being very diverse, all present similar limitations to the standard methods, while not taking profit of the richness of the whole CGM data.…”
Section: Introductionmentioning
confidence: 99%